Das Blaue Buch Chemotherapie-Manual Hämatologie und Onkologie - Engelhardt, Monika; Berger, Dietmar P.; Mertelsmann, Roland; Duyster, Justus (Springer Nature, 2016)
Oncology, Hematology, Pharmacy, Nursing